Criteria for assessment of the residual value of fertilizer phosphorus - Sahrawat, K.L. (2000)
Sorghum yield and P uptake response data from a field experiment conducted at the ICRISAT farm, Patancheru (near Hyderabad) consecutively for four years (1987–1990) were used for determining the residual value of fertilizer P under rainfed cropping on a Vertisol acutely deficient in P. There were seasonal differences in the residual values of P. But more importantly, the residual P value varied depending on the criteria employed for crop response. On an average, the residual value of fertilizer P in the succeeding season was 52 per cent as effective as the fresh P when dry matter yield response was used as the criterion. The residual value of applied P was found to be 47 per cent as effective using grain yield response as the criterion, and the residual P was only 35 per cent as effective as the fresh P when total P uptake response was used as the criterion. It is suggested that the dry matter yield response of sorghum is a simple and practical criterion for determining the residual value of fertilizer P under rainfed cropping.